Предмет: Алгебра, автор: Стасян96

решите 2 производных!!!

Приложения:

Ответы

Автор ответа: Yena
0

f ' (x)=frac{frac{1}{x}(1+lnx)-lnx*frac{1}{x}}{(1+lnx)^2}=frac{frac{1}{x}+frac{1}{x}lnx-frac{1}{x}lnx}{(1+lnx)^2}=frac{frac{1}{x}}{(1+lnx)^2}=frac{1}{x(1+lnx)^2}

 

f ' (x)=2lnsqrt{x^2+1}*frac{1}{sqrt{x^2+1}}*frac{1}{2sqrt{x^2+1}}*2x=frac{4xlnsqrt{x^2+1}}{2(x^2+1)}

 

................................................................................................................................

Похожие вопросы
Предмет: Математика, автор: dzamalbekovaalia
Предмет: Математика, автор: Аноним